2022
DOI: 10.1111/and.14419
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune‐inflammation index, neutrophil‐lymphocyte ratio and platelet‐lymphocyte ratio are predictors of sperm presence in microdissection testicular sperm extraction

Abstract: Infertility is a rising global health issue which has a deep impact on couples' psychosocial life and male factors cover about 50% of all infertility causes (Persily et al., 2021). Azoospermia, defined as the absence of spermatozoa in the ejaculate, is seen ~1% of all male population and this rate is increased up to 10% in men seeking solutions for infertility complaints (Kavoussi et al., 2020). Etiologically, azoospermia can be subdivided into two categories as obstructive and non-obstructive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In this study, the NLR, a universal inflammatory marker, was an independent predictor of PSR with a cutoff value of ≤1.82, whereas the PLR was not. Although a few studies have reported the association of NLR or PLR with the SR rate in nonobstructive azoospermia patients with a normal karyotype [ 24 25 ], to the best of our knowledge, the present study is the first to report the NLR as an independent predictor of SR in KS patients undergoing mTESE.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, the NLR, a universal inflammatory marker, was an independent predictor of PSR with a cutoff value of ≤1.82, whereas the PLR was not. Although a few studies have reported the association of NLR or PLR with the SR rate in nonobstructive azoospermia patients with a normal karyotype [ 24 25 ], to the best of our knowledge, the present study is the first to report the NLR as an independent predictor of SR in KS patients undergoing mTESE.…”
Section: Discussionmentioning
confidence: 60%
“…Numerous studies have investigated the predictive potential of FSH [8] , [11] , [12] , [13] , [14] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] . Given that FSH directly stimulates Sertoli cells within the testes to initiate spermatogenesis, the hypothesis emerged that FSH levels might serve as an indicator of testicular function and thus of the success of SR at mTESE [10] , [21] .…”
Section: Discussionmentioning
confidence: 99%